Determining the Time Required to Achieve Peak Cycloplegic Effect of Cyclopentolate 1% in Children - كردغلي نجوى; يوسف حبيب; حنا يولا (Latakia University Journal -Medical Sciences Series, 2020)
Purpose: To determine the time required to achieve peak cycloplegic effect of cyclopentolate 1% in children, and evaluate the correlation between this time and each of pupillary reaction, pupillary diameter and refractive status of the patient. Patients and methods: This was an analytical cross-sectional study involving children aged 6 to 15 years with dark irides who were attending ophthalmology clinic in Tishreen University Hospital in Lattakia. Cyclopentolate 1% was installed three time at 10-minute intervals. The spherical equivalent, pupillary reaction, and pupillary diameter were recorded before the first drop and nine times after the last drop at 10-minute intervals. The time required to achieve peak cycloplegic effect was defined as the time point at which the spherical equivalent reached and remained within the equivalence limit (0.25 D) of the final value at 110 minutes. Results: 58 children (116 eyes) were enrolled in this study. Their mean age was 9.8 years (range: 6-15 years). The time required to achieve peak cycloplegic effect was 40 minutes after the first drop of cyclopentolate. A poor correlation was observed between the time of peak cycloplegic effect and the pupillary reaction ( r= 0.03). And the peak cycloplegic effect was reached earlier than the maximum pupillary dilatation. Conclusion: In most children, the peak cycloplegic effect of cyclopentolate was 40 minutes after the first instillation. The absence of a pupillary reaction or the maximum pupillary dilatation should not be used as an indicator of maximum cycloplegia.